Capital market supply and REITs' financing and investment decisions. Issue 2 (1st April 2014) - Bai, Qing; Chang, Qingqing; Devine, Avis
Abstract : Purpose: – In the wake of the recent financial crisis, there has been extensive commentary regarding the rise and fall of REIT leverage, how much debt REITs should use, and the trendy "deleveraging" practice among REIT managers. The paper aims to discuss these issues. Design/methodology/approach: – Identifying the late 2000s credit crunch as a supply shock, the paper uses difference-in-difference methodology to isolate alternative firm financing strategies and investment decision responses to the shock. Findings: – Consistent with corporate survey results, this empirical analysis suggests that changes in capital structure are largely supply driven, and REIT managers "time" the debt market in response to credit conditions. Originality/value: – This research clarifies the causes of the documented leverage pattern and provides fresh insights about REIT capital structure.